PENINGKATAN KUALITAS LAYANAN TELLER GUNA MENCAPAI KEPUASAN NASABAH PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK, UNIT TELUK DALAM BANJARMASIN - Novi Shintia; Putri Rizki handayani (At-Tadbir : jurnal ilmiah manajemen, 2017)
The aim of this studies is to understand how teller-service at PT Bank Rakyat Indonesia (Persero) Tbk, Unit Teluk Dalam in Banjarmasin related to service that should be provide at PT Bank Rakyat Indonesia (Persero) Tbk, Teluk Dalam Unit Banjarmasin. The research method used qualitative with the form of descriptive research. Data source used is primary data and secondary data. Variables used in this study are independent and dependent variables. Data collection techniques in this study by means of observation, questionnaires, and documentation. Technical analysis of data that the authors use is qualitative by linking the theory relevant to the problem under study to be understood and used as the basis for solving the problem. The results of this study show that customers in PT Bank Rakyat Indonesia (Persero) Tbk, Teluk Dalam Unit in Banjarmasin are at the point of satisfaction, it can be seen from tangible aspects that strongly agree as much as 44%, empathy aspect agree as much as 36%, reability aspects agree as much 52%, responsiveness aspect agreed as much as 51%, and on assurance aspect agreed as much as 43%.Keywords: Quality of Service, Teller, and Customer.